Patient’s delay in oral cancer: a systematic review - Scott SE, Grunfeld EA, McGurk M. (Blackwell Synergy, 2006)
Detecting oral cancer at an early stage is the most effective means of improving survival and reducing morbidity from this disease, yet a significant proportion of patients delay seeking help after the self-discovery of symptoms of oral cancer.